Correct Fixed-capital Replacement in Input-output Growth Models - Gossling, W. F. (Review of Economic Studies, 1974)
Journal Article Correct Fixed-capital Replacement in Input-output Growth Models Get access W. F. Gossling W. F. Gossling University of East Anglia and West Virginia University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 4, October 1974, Pages 525–531, https://doi.org/10.2307/2296702 Published: 01 October 1974